ISSUES OF ORGANIZING THE PASSENGER TRANSPORTATION ON US RAILWAYS - Korobiova, R. H. (Science and Transport Progress, 2017)
Purpose. The paper focuses on a study of the US railway transport organization management during passenger transportation. Methodology. Studies were carried out on the basis of the analysis of literature sources and reporting data on passenger transportation in the USA. Findings. Negative trends in the work of the passenger complex of the Ukrainian railways are the slowdown in the volumes of transportation, the progressive aging of the rolling stock and the overall activity running at a loss for Ukrzaliznytsia. In this regard, the actual task for domestic rail transport is the implementation of industry reforms. Therefore, the paper presented the study of the experience of organizing the passenger transportation on US railways, whose peculiarity is the extremely high degree of competition between modes of transport. As a result of the conducted analysis for working conditions of the US and Ukrainian railways, the general conditions for the functioning of the railways in both countries connected with passenger transportation securing have been established. It was found that general condition for execution of railway passenger transportation for the United States and Ukraine is the subsidization of this activity and combined use of infrastructure for the freight and passengers’ transportations. In this connection, when developing approaches to reforming the passenger economy of Ukraine's railways, it is advisable to use the experience of the United States in assessing the social effectiveness of rail transport, the impact of passenger transportation on the conditions of freight trains handling, and combined use of railway infrastructure by freight and passenger companies. Originality. The author determined the general trends in the development of passenger railway transportation in the US and Ukraine. Practical value. The resulted methods of organizing the operation of the US railway passenger transportation complex can be adapted to solve problems in the development of passenger transportation on the Ukrainian railways.